On the multi-scale interactions between an offshore-wind-turbine wake and the ocean-sediment dynamics in an idealized framework – A numerical investigation. (January 2018) - Nagel, T.; Chauchat, J.; Wirth, A.; Bonamy, C.
Abstract: We investigate the turbulent dynamics of the coupled atmosphere-ocean-sediment system around a wind turbine. To this end, a coupled two-dimensional idealized numerical model of the ocean and sediment layers, forced by an idealized offshore wind turbine wake is used. The turbine wake impacts the ocean surface and for strong wind and water layer thickness higher than 20 m, large scale eddies of the size comparable to the wake thickness are generated, leading to a turbulent dynamics in the ocean. The turbulence in the ocean is controlled by the shallow wake parameter S. The turbulent ocean dynamics is numerically integrated using time dependent simulations at fine horizontal resolution (1 m). From these simulations, eddy coefficients parametrizating the turbulent fluxes are proposed to be used in larger-scale (RANS) models. The ocean dynamics and the parameter values depend mainly on S. The ocean dynamics is laminar (S > 7.10 −2 ), has a localized (7.10 −2 <S < 7.10 −2 ) or domain wide turbulent (S < 3.10 −2 ) behavior. In the first two cases, changes in seabed elevation are around a few millimeters per month. For the third case, averaged over several days, changes decreases to a few tenths of millimeters per month. This is due to the alternating local velocity which transports sediments back and forth. Highlights: The turbine wake has an impact on both the ocean and the seabed dynamics. The turbine wake impact on the ocean surface generate instabilities and vortex streets. A phenomenological law for the non−dimensional eddy viscosity has been proposed. The wake presence is responsible for seabed sand erosion and deposition. The ocean dynamics is important for the energy budget around wind turbines.